Real world evidence on the characteristics of regular and intermittent users of a very‐low calorie diet program and associations with measures of program success, health, and quality of life - Patrice Jones; Michelle Blumfield; Emma Beckett; Skye Marshall; Kylie Abbott; Emily Duve; Flavia Fayet‐Moore (Wiley, 2024)
Abstract Background Very low‐calorie diet (VLCD) programs are readily available in Australia. However, there is a lack of real‐world evidence describing the characteristics related to positive outcomes. Aims To examine the demographic, eating, self‐efficacy and program engagement characteristics of VLCD users in Australia, and the associations between user characteristics and program success, weight loss, quality of life (QOL) and health. Method Cross‐sectional data from Australian adults: regular users (n = 189: VLCD user ≥4 days/week for >4 weeks) and intermittent users (n = 111, VLCD user <4 weeks and/or <4 days/week). Self‐reported data on demographics, VLCD program use, support, eating behavior, weight‐related QOL, mental health, physical health, self‐efficacy, and physical activity. Descriptive and inferential statistics were performed in R. Results Compared to regular users, intermittent users reported lower percentage weight loss (15.1% ± SD 9.8 vs. 9.9% ± SD 6.8, relative to starting weight), fewer reported their VLCD program as very successful (44% vs. 35%), higher depressive symptom scores (8.7 ± SD 2.8 vs. 6.7 ± SD 5.1), and lower general self‐efficacy (23.9 ± SD 4.7 vs. 29.4 ± SD 5.7), nutrition self‐efficacy (11.9 ± SD 2.0 vs. 14.5 ± SD 3.1) and weight‐related QOL scores (60.9 ± SD 22.2 vs. 65.0 ± SD 11.8; p < 0.001 for all). In regular users, older age and longer program duration were associated with greater total weight loss, support, and program success (p < 0.001 for all). In intermittent users, program success was greater when dietitian support was used (odds ratio [OR] 6.50) and for those with higher BMIs (OR 1.08, p < 0.001 for all). In both groups, more frequent support was associated with better weight‐related QOL (p < 0.001). Conclusion This study provides real‐world evidence that regular VLCD users had greater success and weight loss than intermittent program users. These findings may be used to tailor and improve the delivery of VLCD programs in Australia and other countries with retail access to VLCDs.